Distribuição de elementos traço nos oceanos atlântico e pacífico utilizando tartarugas marinhas (chelonia mydas) como espécie sentinela - Fraga, Nairana Santos (2023)
The environmental fuel and the contribution of elements drawn on the globe have increased in recent times. The quantification of trace elements has been carried out in animals all over the world. C. mydas is a species with a long life cycle, which allows these elements to bioaccumulate over the years. Because it is a species with coastal habits in its juvenile phase, it was used as a bioindicator for inference about the distribution of characteristic elements. Contents of zinc, copper and a discussion on cadmium were considered using specimens of C. meu origins from published works carried out in Brazil, United States, Hawaii, Japan and Australia. Liver, kidney and muscle comparisons of 35 individuals were used in the comparative analyses, with 7 animals from each locality belonging to the same size class for comparisons between oceans of origin. Zinc, copper and cadmium were detected in all samples, with the highest rate in liver (zinc and copper) and kidneys (cadmium). No muscle for the three lower grade metals were found. The Brazilian specimens obtained the lowest averages both in the liver, kidney and muscle. In the two comparative analyzes carried out (direct and additional) of animals from Brazil-Rio Grande do Sul, they showed lower levels with a possible visualization of patterns of hemispheres for copper. All metals have adopted a global distribution. For all elements, the selection methodology of 7 individuals for each location was important in the visualization of patterns.